THE IMPLEMENTATION OF TRACER STUDY AT TERTIARY EDUCATION INSTITUTIONS: A REVIEW OF RECENT LITERATURE - Syahrul Fahmy; Wan Roslina; Nurul Haslinda; Rozila Umar; Norzamziah Afzainizam, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Tracer study has emerged as a critical tool for education institutions to assess the relevance of their academic programs and the employability of their graduates. By tracking the post-graduation experiences of alumni, these studies provide valuable insights into the alignment between academic programs and industry needs. The primary problem addressed in this article is the need for an updated and structured view of how tracer study is implemented at these institutions. To achieve this, an extensive search of scholarly articles from Scopus, Web of Science and Science Direct was carried out, focusing on studies published between 2022 and 2024, using the PRISMA framework. A total of 26 final data was analysed. Findings were divided into three themes namely graduate employability; technical innovations; and competency development. This review has revealed that it is essential to bridge the gap between academia and industry to enhance graduate employability. This can be achieved through initiatives such as industry partnerships, internships, and work-integrated learning programs. The use of machine learning models and predictive analysis tools can provide valuable insights into graduate outcomes, enabling education institutions to make informed decisions to improve student preparation and curriculum development. Soft skills, such as critical thinking and communication are highly valued by employers and can significantly impact graduate employability. Education institutions should prioritize the development of these skills through a variety of pedagogical approaches, including experiential learning, group work, and case studies.